L‐band depolarised radar back scattering from Martian topographic surface: A numerical study - Ying Yang; Yu Liu; Kun‐Shan Chen; Jingwen Li (IET Radar, Sonar & Navigation, 2021)
Abstract The interaction of radar signals with a planetary surface is critical for the utility of radar data. Herein, a power‐law roughness spectrum is used to model the roughness and an inhomogeneous vertical permittivity to describe the dielectrics from the surface of Mars. Numerical simulations of depolarised radar backscattering are then conducted. To gain a more complete picture of depolarised characteristics, a wide range of surface roughness is considered. Results reveal that the depolarised backscattering is sensitive to the dielectric profiles with –10 dB is observed. The polarization conversion ratio, the ratio of depolarisation to total polarization backscattering, is a sensitive indicator of dielectric profiles and roughness, and thus is useful in retrieving dielectric profile.